2021
DOI: 10.1155/2021/7230063
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Emergent Transcatheter Aortic Valve Implantation in Patients with Acute Decompensated Aortic Stenosis: Systematic Review and Meta-Analysis

Abstract: Introduction. The aim of this systematic review and meta-analysis was to investigate the efficacy and safety of emergent transcatheter aortic valve implantation (TAVI) in patients with decompensated aortic stenosis (AS) by comparing the clinical outcomes with the patients who had received the elective TAVI. Methods. By searching PubMed, EMBASE, and Cochrane databases, we obtained the studies comparing the clinical outcomes of emergent TAVI and elective TAVI. Finally, 14 studies were included. Results. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…With regard to performing urgent/emergency TAVI, there are reports of acceptable outcomes being achieved and encouraging its use; 8 in contrast, others have reported that urgent/emergency TAVI has a worse prognosis, with more complications than elective TAVI, and should be carefully considered in individual cases. 7 The point estimate in the report from the Optimized CathEter vAlvular iNtervention-TAVI (OCEAN-TAVI) Registry 8 was in an urgent/emergency situation, highly frail patients with low albumin concentrations may achieve fewer benefits from TAVI, as observed in the present study.…”
Section: Comparison Between Urgent/emergency and Elective Tavisupporting
confidence: 52%
See 1 more Smart Citation
“…With regard to performing urgent/emergency TAVI, there are reports of acceptable outcomes being achieved and encouraging its use; 8 in contrast, others have reported that urgent/emergency TAVI has a worse prognosis, with more complications than elective TAVI, and should be carefully considered in individual cases. 7 The point estimate in the report from the Optimized CathEter vAlvular iNtervention-TAVI (OCEAN-TAVI) Registry 8 was in an urgent/emergency situation, highly frail patients with low albumin concentrations may achieve fewer benefits from TAVI, as observed in the present study.…”
Section: Comparison Between Urgent/emergency and Elective Tavisupporting
confidence: 52%
“…Although previous studies reported on the feasibility of urgent/emergency TAVI in selected patients with decompensated AS, it has also been reported that the prognosis of patients requiring urgent/emergency TAVI is significantly worse than for patients undergoing elective TAVI. 6, 7 Conversely, a previous report from a large-scale registry in experienced centers demonstrated that emergency TAVI was not independently associated with 1-year mortality. 8 T he number of patients with aortic stenosis (AS) has increased rapidly due to the incremental increase in the elderly population globally.…”
mentioning
confidence: 89%
“…Table 3 provides a summary of the main results of these studies. A meta-analysis including 14 studies reported higher incidence of 30-day, in-hospital, and 1-year mortality after emergent than elective TAVR [ 43 ]. Performing TAVR in the setting of acute clinical decompensation requires some deviations from standard organizational pathways.…”
Section: Tavrmentioning
confidence: 99%
“…Previous studies showed that in patients with AS, hospitalization for acute decompensation is associated with poor outcomes [2,3,5], and some data point to a better prognosis in this cohort of patients if treated with SAVR (33% 5-year mortality, 23.2% HF hospitalization) compared to conservative management (75.3% 5-year mortality, 70.4% HF hospitalization), although the results are still worse than in elective procedures (17.3% 5-year mortality, 4.8% HF hospitalization) [5]. Robust data concerning TAVI outcomes in this specific population are limited, and there are discrepancies in the published studies, with most of them showing worse outcomes (mortality, acute kidney injury, bleeding, rehospitalization) [5,[11][12][13] in urgent procedures, but with few data suggesting similar results concerning mortality, hospitalization and other adverse events [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first percutaneous aortic valve was implanted in 2002, a significant evolution in TAVI technology has occurred, allowing the treatment of more patients, from low-to very-high risk [6][7][8][9][10]. Despite that, there is still some uncertainty regarding TAVI results in patients submitted to urgent procedures, with most literature suggesting that this subgroup of patients tend to have worse results, but some data pointing to similar outcomes [5,[11][12][13][14][15]. There is also a gap in the guidelines concerning aortic valve replacement in this acute setting, with only a brief recommendation for aortic balloon valvuloplasty as a bridge to TAVI or surgical aortic valve replacement (SAVR) in decompensated AS [16].…”
Section: Introductionmentioning
confidence: 99%